Test of Liquid Soap Stirrer of Soap Made from Used Cooking oil With Extract of Lemongrass, Pandan and Lemon - Faris Faisal Rahman; Ainun Rohanah; Saipul Bahri Daulay (Universitas Sumatera Utara, 2016)
Use cooking Oil is the remains of frying oil that can not be reused. Therefore a further processing is needed, one of them is to be come liquid soap. The aim of this study was to process used cooking oil into liquid soap using the extract of lemongrass, pandan and lemon. The study was conducted at the Laboratory of Agricultural Engineering and parameters tested at the Food Chemical Analysis Laboratorium Faculty of Agricultural in April 2015 to Mei 2015 by using a non-factorial completely randomized design. Parameters measured were water content, free fatty acid (FFA), alcohol insoluble part, and organoleptic test. The result showed that extract of lemongrass, pandan and lemon extract had no significant effect on water content, free fatty acid (FFA) and alcohol insoluble part. Keywords: used cooking oil, liquid soap , extract of lemongrass, pandan, lemon